Management of anterior crossbite in mixed dentition using sloped composite resin: a case report - Sanjaya, Devita; Kuswandari, Sri (Padjadjaran Journal of Dentistry, 2026)
Introduction: Dental-type anterior crossbite is a malocclusion involving an individual tooth, in which the maxillary incisor is positioned lingual to the mandibular incisor without skeletal discrepancy. Its most common aetiology is persistence of a primary tooth, which may disrupt the eruption path and lead to palatal eruption of the permanent successor. Sloped composite resin is a simple and effective method for correcting an anterior crossbite. In the cases presented, the dental crossbite was corrected by applying a 3-4 mm bonded resin-composite inclined plane to the incisal edge of the mandibular incisors at an angle of approximately 45° to the long axis of the tooth. This case report aimed to describe the management of dental-type anterior crossbite involving individual teeth using sloped composite resin in children during the mixed dentition period. Case report: Three cases of anterior crossbite were managed in three paediatric patients. The first case involved an 8-year-old boy with a crossbite affecting teeth 11 and 21. The second case involved an 8-year-old boy with a crossbite of tooth 21, and the third case involved a 7-year-old girl with a crossbite affecting teeth 11 and 21. All patients had good oral hygiene and no deleterious oral habits. The available arch space exceeded the mesiodistal width of the affected incisors. Sloped composite resin was applied to the antagonist mandibular incisors, either directly or indirectly, at an angle of approximately 45° to the long axis of the tooth. On average, the crossbites were corrected within two weeks. Conclusion: This case report demonstrates that direct and indirect sloped composite resin applications can provide rapid and consistent correction of dental-type anterior crossbite during the mixed dentition period. The technique was effective, minimally complex and clinically practical, with an average correction time of two weeks.